The Effect of E-Samsat Effectiveness, Progressive Taxes and Samsat Outlet Service Quality on Motor Vehicle Taxpayer Compliance - Meilan, Ervina; Meitri, Della; Imanisa, Ikhnandiena Nur; Mayang, Yalfa (SINTESA, 2024)
The effectiveness of E-Samsat concerns the success of supporting a motor vehicle tax collection process in order to achieve the predetermined target by simplifying and shortening the time to pay motor vehicle taxes by using the E-Samsat service which can be done anywhere and anytime. that the realization of motor vehicle tax (PKB) in Sumedang Regency in 2020-2022 tends to be unstable. This study uses a quantitative method. This sampling technique was carried out by random sampling. The data sources in this study include primary and secondary data, where the data sources provide data directly to data collectors. Secondary data in this study is using a questionnaire through a google form. The results of this research are expected to provide a deeper understanding of Motor Vehicle Tax, as well as contribute to providing an understanding of taxation in the payment of Motor Vehicle Tax. Good service, transparent progressive tax structure, efficient effectiveness can increase tax revenues in the transportation sector. The e-Samsat program is a very effective innovation to make it easier for taxpayers to pay motor vehicle taxes, so that the public or taxpayers are aware and compliant of the importance of carrying out the obligation to pay motor vehicle taxes. The quality of service must also always be improved and improved so that taxpayers feel comfortable when paying samsat. So that it can increase local original income which is then redistributed for the welfare of the community.